Incidence of reactive thrombocytosis in serious bacterial infections in children aged two months to twelve years and its usefulness as a predictor of serious bacterial infections - Sadique, Thahseen Nilofar Sahubar; Natarajan, Thrilok; Shanmugham, Kabilan; Veluchamy, Suresh Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: The aims of the study were to estimate the incidence of reactive thrombocytosis(RT) among febrile children aged 2 months to 12 years and to identify any differences in age group and gender in mounting thrombocytosis as a response to infection, to identify if thrombocytosis occurred preferentially in any particular group of serious bacterial infections(SBI), to compare thrombocytosis with other parameters like total white cell count, C-reactive protein(CRP), cultures etc. and to assess the utility of platelet count as a potential predictor of serious bacterial infection. Methods: This was a prospective study done in Institute of Child Health and Hospital for children, Madras Medical College from September 2015 to July 2016. Inclusion criteria: Children aged 2 months to 12 years with symptoms of fever less than 6 days admitted in the paediatric wards and those seen at the outpatient department. Exclusion criteria: Children having received parenteral antibiotics. Results: Of the 500 children, 142 (28.4%) had reactive thrombocytosis. RT was mild in 120 children (24%), moderate in 16 children (3.2%), severe in 4(0.8%) and extreme in two children (0.4%). This study showed that 36.48% (85 / 233) of children under 1 year had RT (p = 0.0002).There was no significant sex related difference in mounting RT. Out of 500 children included in the study, serious bacterial infection was diagnosed among 171 children (34.2%).Pneumonia (n=100) was the most common SBI followed by urinary tract infections (n=33), meningitis (n=23), sepsis (n=15). This study showed that RT has a moderate ability to predict serious bacterial infections (AUC=0.78; PPV-75.35%). Conclusions: Incidence of reactive thrombocytosis in febrile children aged 2 months to 12 years is 28.4%. It occurs more frequently in infants and without any sex predilection. RT is associated with leucocytosis, positive CRP, positive Chest X ray findings, positive urine culture and positive CSF findings. This shows that RT has a moderate ability in predicting SBI in children.